PDGF and TGF-β contribute to the natural course of human IgA glomerulonephritis - Niemir, Zofia; Stein, Henning; Noronha, Irene L.; Krüger, Cornelia; Andrassy, Konrad; Ritz, Eberhard; Waldherr, Rüdiger (Kidney international, 1995)
PDGF and TGF-β contribute to the natural course of human Ig-A glomerulonephritis. PDGF and TGF-β are known mediators of mesangial cell proliferation and matrix expansion. The presence of these regulatory factors was examined in 30 renal biopsies from patients with IgA glomerulonephritis (IgA-GN) at the mRNA and protein level. Normal renal tissue served as control. The mRNA expression of PDGF A/B chains, PDGF-βR and TGF-β1 was evaluated by means of RT/PCR with subsequent Southern blot hybridization and/or non-radiactive in situ hybridization. In addition, PDGF-AB/BB, PDGF-βR, TGF-β isoforms (β1, β1+2, β2+3), the small TGF-β1 latency associated peptide (TGF-β1 LAP) and the extracellular matrix proteins tenascin and decorin were analyzed by immunocytochemistry. The expression of growth factors was correlated with light microscopic and clinical features. Compared to normal control kidneys, an increased expression of PDGF-BB/PDGF-βR mRNAs and the corresponding proteins was observed in all biopsies with IgA-GN. Up-regulation was related to the degree of glomerular proliferation and the extent of fibrosing interstitial lesions. In contrast, there was a discordance between TGF-β1 mRNA and protein expression (evaluated by immunocytochemistry). In all biopsies, irrespective of the stage of the disease, abundant TGF-β1 transcripts were detected, whereas TGF-β1 immunoreactivity was expressed to a lesser degree and disclosed a more variable staining pattern. In patients with significant proliferative glomerular lesions and minor tubulointerstitial alterations, TGF-β1 positivity was confined to areas of glomerular proliferation, whereas in cases with more severe histology including sclerosing lesions TGF-β1 immunoreactivity was less prominent. The distribution and the intensity of TGF-β1 LAP staining commonly exceeded the positivity noted for TGF-β1, indicating only limited TGF-β1 activation. A decreased reactivity for tenascin accompanied the morphological features of glomerular sclerosis. The staining patterns and the fact that only very few inflammatory cells, particularly CD68 positive monocytes/macrophages, were detected in glomeruli confirm that predominantly resident glomerular cells (mesangial and endothelial cells) are the major source of up-regulated growth factor production in IgA-GN. Since the expression of PDGF-AB/BB paralleled the severity of proliferative glomerular changes, PDGF seems to represent a potential indicator of activity in this condition. It is suggested that an imbalance between PDGF and TGF-β (by restricted translation and/or activation) production contribute to the progressive nature of IgA-GN.
Artikelversion: 16. Dezember 2015
Gesehen am 30.10.2023